PENGEMBANGAN MEDIA PETRA (PETA NUSANTARA) BERBASIS COOPERATIVE LEARNING PADA KELAS IV DI SDN PENJARINGAN 03 JAKARTA UTARA - Putri Yohana; Nidya Chandra Muji Utami; Arita Marini (JURNAL HANDAYANI PGSD FIP UNIMED, 2023)
The Development Of Learning Media In Form Of Board Games Based On Cooperative Learning In The Content Of Social Studies Learning Grade IV Elementary School. This research and development aims to develop a learning media called "PETRA (Peta Nusantara)" based on cooperative learning in Social Sciences learning content for students in Grade IV of Elementary School. Respondents participated in this study were media expert, material expert, linguist, and students. This research happened when it was still limited face-to-face learning due to pandemic, the trials were accomplished on students which included the one-to-one test, small group test, and field trials (field test). This study uses the research and development (RnD) method with the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). Data collection techniques used are observation, interviews, and questionnaires. The validation results of media expert obtained a score of 96%, material expert validation obtained a score of 90%, and linguist validation obtained a score of 82.5%. In the stage of one-to-one trial a score of 100% was obtained, the small group trial stage obtained a score of 100%, and the field trial stage obtained a score of 98.9%. The results of the effectiveness test based on the pre-test and post-test showed the results "There are differences in outcomes of the student learning before and after using cooperative learning-based PETRA media in Indonesian culture-laden lesson in grade IV Elementary School" with the results t.count (9.17) > t.table ( 2,17). Based on these results, it can be interpreted that the learning board media PETRA (Peta Nusantara) achieves an excellent criteria, very proper, and is effectively used as a cooperative learning-based learning media in Social Studies learning content in class IV Elementary School.Keywords: Learning Media in Form of Board Games, Cooperative Learning, Social Studies, Grade IV Elementary School Pengembangan Media PETRA (Peta Nusantara) Berbasis Cooperative Learning Dalam Muatan Pembelajaran Ilmu Pengetahuan Dasar Kelas IV Sekolah Dasar. Penelitian dan pengembangan ini bertujuan untuk mengembangkan media pembelajaran “PETRA (Peta Nusantara)” yang berbasis pembelajaran kooperatif dalam muatan pembelajaran Ilmu Pengetahuan Sosial untuk peserta didik kelas IV Sekolah Dasar. Responden yang dilibatkan dalam penelitian ini yaitu ahli media, ahli materi, ahli bahasa, dan peserta didik. Penelitian ini dilaksanakan ketika masih pembelajaran tatap muka terbatas (PTMT), uji coba yang dilaksanakan pada peserta didik yaitu tahap uji coba satu-satu (one-to-one test), uji coba kelompok kecil (small group test), dan uji coba lapangan (field test). Penelitian ini menggunakan metode penelitian dan pengembangan (RnD) dengan model ADDIE (Analyze, Design, Development, Implementation, dan Evaluation). Teknik pengumpulan data yang digunakan yaitu observasi, wawancara, dan kuesioner. Melalui hasil validasi ahli media diperoleh skor sebesar 96%, validasi ahli materi diperoleh skor sebesar 90%, dan validasi ahli bahasa diperoleh skor sebesar 82,5%. Pada tahap uji coba one-to-one diperoleh skor sebesar 100%, tahap uji coba small group diperoleh skor sebesar 100%, dan tahap uji coba field diperoleh skor sebesar 98,9%. Hasil uji efektivitas berdasarkan pre-test dan post-test menunjukkan hasil “Terdapat perbedaan hasil belajar peserta didik sebelum dan sesudah menggunakan media PETRA berbasis cooperative learning pada muatan pelajaran keanekaragaman budaya Indonesia di kelas IV SD” dengan hasil thitung (9,17) > ttabel (2,17). Berdasarkan hasil tersebut, dapat disimpulkan bahwa media papan belajar PETRA (Peta Nusantara) mencapai kriteria sangat baik dan layak, serta efektif digunakan sebagai media pembelajaran berbasis cooperative learning pada muatan pembelajaran Ilmu Pengetahuan Sosial di kelas IV Sekolah DasarKata kunci: Media Pembelajaran Papan Bermain, Pembelajaran Kooperatif, Ilmu Pengetahuan Sosial, Sekolah Dasar